284 Understanding the impact of adverse childhood experiences on health and wellbeing in England. (1st September 2016) - Ford, Kat; Quigg, Zara; Hughes, Karen; Butler, Nadia; Bellis, Mark A
Abstract : Background: An emergent body of research is underlining the long-term impacts that adverse childhood experiences (ACEs) have in determining the health and social prospects of individuals. ACEs are now considered one of the strongest predictors of poor health and social outcomes in adults. Individuals with higher numbers of ACEs are found to have higher risks of anti-social behaviour, crime, and violence, and are at increased risk of developing a range of health conditions and ultimately premature mortality. Methods: A household survey was conducted with 5, 454 residents aged between 18 and 69 in the United Kingdom in the areas of Northamptonshire, Hertfordshire and Luton during the period June to September 2015. The survey explored childhood experiences before the age of 18, past and current health and social behaviours and outcomes. Results: Four in ten (43.1%) of all individuals surveyed experienced at least one of the nine ACEs examined. The independent impact of ACEs on health and criminal justice outcomes will be discussed, including the increased risks of harmful behaviours, morbidity and mortality in adulthood from the number of ACEs. The associations between ACEs and socioeconomic markers will be identified. The presentation will provide an overview of the burden of harmful behaviours that would be prevented in the absence of ACEs. Findings across the study areas will be discussed in relation to prevalence of ACEs found in other research within the United Kingdom. Conclusions: The implications of the research findings on interventions to improve health and reduce inequalities will be highlighted. The importance of service planning and effective investment in early years at a local and national level to prevent ACEs and ensure the provision of positive childhood environments for future generations will be addressed.